Effectiveness of bylaws in the management of natural resources: The West African experience - Alinon, Koffi; Kalinganire, Antoine (International Food Policy Research Institute, 2008)
The role of various stakeholders in the management of natural resources is not clear in the West African countries. This paper discusses the historical changes in power delegation from central origins to peripheral institutions. The analysis covers the rise of bylaws across the Western African countries and links the multiplicity of bylaws to the amplification of the decentralization movement. On the basis of a literature review and their own practitioners’ experiences, the authors demonstrate the pertinence of bylaws as a tool for better management of natural resources. In the West African Francophone context, bylaws could stand both for regulations enacted by decentralized authorities or “local conventions” binding village community groups. Where formal bylaws suffer from limited enforcement, local people continue, through their traditional representatives, to engage in the negotiation of local conventions for the management of natural resources. According to the authors, there is a need to recognize local conventions, which offer an opportunity for decentralization to be more rooted in local situations. Through such conventions, traditional institutions prove their ability to reshape with decentralization even if decentralization reforms and national forestry laws have ignored them across West Africa.